2017
DOI: 10.4236/jpee.2017.510001
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Analysis of a Solar Absorption Refrigeration System in Ngaoundere

Abstract: In this study, the first and second laws of thermodynamics are used to analyze the performance of a single-stage absorption refrigeration system powered by solar energy. The working pair used in this study is LiBr-H 2 O where water (H 2 O) is the refrigerant and the lithium bromide (LiBr) is the absorbent. A mathematical model based on exergy analysis is applied to analyse the system performance. Temperature, enthalpy, entropy, mass flow rate and exergy loss of each component including evacuated tube solar col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Ambient temperature and Solar insolation in Ngaoundere on the 15th of January 2014 [19]. Table 1 gives the solar insolation and the ambient temperature collected in the Meteological Station of Ngaoundere on the 15th of January 2014 by M. Tenkeng [19]. Table 2 presents the temperature of the components of the system at 12.30 PM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambient temperature and Solar insolation in Ngaoundere on the 15th of January 2014 [19]. Table 1 gives the solar insolation and the ambient temperature collected in the Meteological Station of Ngaoundere on the 15th of January 2014 by M. Tenkeng [19]. Table 2 presents the temperature of the components of the system at 12.30 PM.…”
Section: Resultsmentioning
confidence: 99%
“…Properties of the LiBr-H 2 O solution and typical overall heat transfer coefficient were adopted from Gur Mittelman [29]. For the heat transfer area or total conductance, we adopted the values from M. Tenkeng et al [19]: (UA)a = 1.800 kW/K, (UA)e = 2.250 kW/K, (UA)g = 1.000 kW/K, (UA)c = 1.200 kW/K. World Journal of Engineering and Technology…”
Section: Input Parameters For the Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the evaporator and generator registered the great losses and were the components that needed to be optimized. Tenkeng et al [11] also presented a study on exergy analysis of a series double effect solar refrigeration in Ngaoundere, Cameroun on a half hourly basis, from 6.30AM to 6.30PM. A thermodynamic analysis was undertaken by simulation with a FORTRAN program and the results showed that the High Pressure Generator and the evaporator were the component needing a great attention in term of exergy efficiency and exergy loss.…”
Section: Introductionmentioning
confidence: 99%